Knowledge and Attitude Regarding Rabies among Community People of Dhamboji -1, Nepalgunj, Banke - Shrestha, Rajani Kumari (Academia Research Journal, 2024)
The virus that causes rabies spreads from one species to another through the saliva or tissues of the nervous system. When the rabies virus affects the central nervous system, it can lead to brain illness, death, and extremely agonizing neurological symptoms. Since rabies is a zoonotic illness, people can get it from other animals. With a 99.9% mortality rate, rabies is the worst illness on the planet. The study's goals were to determine the community members' knowledge and attitudes about rabies in Dhamboji-1, Nepalgunj, Banke. The study employed a descriptive cross-sectional research methodology, and sixty general residents of Dhamboji-1, Nepalgunj, Banke were chosen using a non-probability purposive sampling approach. For collecting data, a structured questionnaire was employed. The information was gathered in the month of Baisakh in 2081. Additionally, SPSS version 20 was used to analyze the acquired data using inferential descriptive statistics. The study's findings show that, when it came to rabies, more than half of the respondents—31, or 51.7% had average knowledge, a quarter18, or 30 % had bad knowledge, and the least11, or 18.3% had strong knowledge. In a similar vein, 25% of respondents 13(22) had a positive attitude, almost 50% of respondents 28(46.7) had a neutral attitude, and over 25% of respondents 19 (31.3) had negative attitude. While no other variable shows a significant relationship between level of knowledge and attitude and demographic variables like age, sex, religion, educational status, level of education, occupation, family monthly income, history of animal bite, if yes, which animal, vaccination status, pet ownership, and if yes, pet owner status, there was a significant association between level of knowledge and attitude and demographic variables like heard about rabies and source of information.